PEMBERIAN VIRGIN COCONUT OIL UNTUK MEMPERCEPAT PROSES PENYEMBUHAN LUKA PERINEUM PADA IBU POSTPARTUM DI PMB N BOJONGGEDE KOTA BOGOR - Hanifa, Fanni; Rumahorbo, Nora Agustina; Putri, Riskiana (Jurnal Kebidanan, 2023)
Childbirth and the postpartum period are processes that are vulnerable to various complications that can harm the mother. One of them is due to a tear in the perineum. Vaginal delivery will be more susceptible to tearing of the perineum to varying degrees. Virgin Coconut Oil (VCO) contains ingredients that can heal wounds in the perineum. This study aims to compare midwifery care for postpartum mothers with second degree perineal injuries regarding the administration of Virgin Coconut Oil (VCO) to accelerate the healing of perineal wounds in postpartum mothers. The research method uses qualitative research with a case study approach. The results of the study proved that after being observed for 5 days, Virgin Coconut Oil (VCO) could heal grade II perineal wounds in postpartum mothers faster than respondents who were not given Virgin Coconut Oil (VCO) healed on the 7th day. The conclusion is that giving Virgin Coconut Oil (VCO) can heal perineal wounds faster than without giving Virgin Coconut Oil (VCO).